Thiol-yne photo-clickable electrospun phase change materials for thermal energy storage - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE BV, 2018)
Fatty acids, fatty acid esters and fatty acid composites have been widely accepted materials as PCMs. In the present work, nanosilica reinforced nanofiber composite was prepared as PCMs. First, polyvinyl alcohol (PVA) and nanosilica was modified with mercaptopropionic acid and 3-(mercaptopropyl)trimethoxysilane respectively and thiolated-PVA-nanosilica nanofibers were prepared by using electrospinning. Stearic acid was used for long chain fatty acid. Then stearic acid was functionalized with propargyl groups to introduce thiol-yne clickable sites. Finally, various amounts of stearic propargyl ester were reacted with thiolated-PVA-nanosilica nanofibers, following to UV-induced thiol-yne click reaction by UV-irradiation at 365 nm between thiol groups of nanofiber and propargyl groups of stearic propargyl ester. The structural characterization was performed by ATR-FTIR spectroscopy. The morphologies of nanofibers after and before modification were investigated by scanning electron microscopy (SEM). It is said that nanofibers have uniform diameter size. Thermal and phase change behaviors of the electrospun nanofibers were investigated. Thiolated-PVA nanofiber showed no phase change behavior. With the addition of stearic propargyl ester increased phase change enthalpy of the PVA nanofibers from 0 J/g to 37 J/g. The freezing cycle phase change enthalpy was also observed and was found between - 13 and - 47 J/g.
Keywords: Energy storage; Nanofiber PCMs; Thiol-yne; Click reaction; POLY(VINYL ALCOHOL); COMPOSITE FIBERS; FATTY-ACIDS; BLENDS; NANOFIBERS; ESTERIFICATION; FABRICATION; CHEMISTRY; SHELL